Left ventricular assist device patient maintained on home hemodialysis: A novel class of patients to the home dialysis population. Issue 3 (23rd January 2018) - Hanna, Ramy M.; Cruz, Daniel; Selamet, Umut; Hasnain, Huma; Kwon, Murray; Baas, Arnold; Wilson, James
Abstract: Severe heart failure is increasingly being managed by cardiac transplantation, and in some cases mechanical support devices serve as destination therapies. Left ventricular assist devices (LVADs) were approved for destination therapy for end stage heart failure patients before the more advanced total artificial heart modality became available. One common complication of mechanical assist device placement is acute kidney injury. Historically, patients with mechanical support devices have had to have inpatient hemodialysis until combined heart kidney transplant. Though, some units have started accepting LVAD patients in outpatient dialysis clinics. The cost of in center hemodialysis remains high and home dialysis modalities are becoming increasingly popular. We report the first patient with an LVAD to undergo training and successful home hemodialysis while awaiting combined heart kidney transplantation.